2017
DOI: 10.1111/1748-8583.12160
|View full text |Cite
|
Sign up to set email alerts
|

“Handle with care”: The mediating role of schedule i‐deals in the relationship between supervisors' own caregiving responsibilities and employee outcomes

Abstract: Drawing on theories of perspective‐taking and i‐deals, this study explores the impact of supervisors' own caregiving responsibilities for elders and parental status on subordinates' schedule i‐deals. Moreover, we investigate the extent to which schedule i‐deals mediate the relationship between supervisors' caregiving responsibilities and two employee outcomes: satisfaction with work–family balance and turnover intentions. Using a sample of 520 dyads involving 137 supervisors and 520 employees, the results of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 76 publications
(102 reference statements)
3
40
0
Order By: Relevance
“…Experiencing the benefits of a better skill-task fit, this manager is likely to acknowledge similar needs of his or her subordinates and assign them tasks that better fit their skills and abilities. Indirectly supporting this argument, a study by Las Heras et al (2017b) demonstrated that supervisors with care giving responsibilities at home are more likely to grant schedule i-deals (a form of i-deals allowing recipients to have work schedule flexibility) to their subordinates. We thus propose:…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Experiencing the benefits of a better skill-task fit, this manager is likely to acknowledge similar needs of his or her subordinates and assign them tasks that better fit their skills and abilities. Indirectly supporting this argument, a study by Las Heras et al (2017b) demonstrated that supervisors with care giving responsibilities at home are more likely to grant schedule i-deals (a form of i-deals allowing recipients to have work schedule flexibility) to their subordinates. We thus propose:…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…However, research on both topics has been mainly carried out in developed Northern Europe countries and the English speaking world. Researchers have studied different aspects related to family‐friendly companies in some Southern European and Latin American countries (e.g., Adame, Caplliure, & Miquel, 2016; Bosch et al, 2018; Las Heras, Van der Heijden, De Jong, & Rofcanin, 2017; Poelmans, Chinchilla, & Cardona, 2003; Rofcanin, Las Heras, Escribano, & Stanko, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, using a sample of 137 supervisors and 520 employees from three organizations (a bank, a private higher education institution and a pharmaceutical Company) from El Salvador, Las Heras et al (2017) examined the mediating role of schedule i‐deals in the relationship between supervisors' caregiving responsibilities and (i) satisfaction with work family balance and (ii) turnover intentions. Results using multilevel analysis show a positive relationship between supervisors' caregiving responsibilities for elders and schedule i‐deals, also noting the mediator role of schedule i‐deals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organisations are steadily increasing the room to individualise working conditions as a result of different trends, such as globalisation, the information economy, the democratisation of workplaces, and a decline in collective bargaining (Bal & Dorenbosch, ). Employees welcome such opportunities for individual treatment as the workforce is becoming more diverse in terms of age, gender, and ethnicity, resulting in differing workplace needs (Liao, Wayne, & Rousseau, ) and is increasingly seeking to be treated as individuals, given their changing needs and preferences (Las Heras, Van der Heijden, De Jong, & Rofcanin, ; Marescaux, De Winne, & Sels, ). This, in fact, has implications for human resource management (HRM) such that organisations are moving away from standardised HR practices, which apply to the entire organisation or a large group of employees, towards a more differentiated approach (e.g., Deloitte HR Trends, ).…”
Section: Introductionmentioning
confidence: 99%